Solve all your doubts with Teachoo Black (new monthly pack available now!)

Miscellaneous

Misc 1
Important

Misc 2

Misc 3

Misc 4 Important

Misc 5 (i) Deleted for CBSE Board 2023 Exams

Misc 5 (ii) Important Deleted for CBSE Board 2023 Exams

Misc 6 Deleted for CBSE Board 2023 Exams

Misc 7 Deleted for CBSE Board 2023 Exams

Misc 8 Important Deleted for CBSE Board 2023 Exams

Misc 9 Deleted for CBSE Board 2023 Exams

Misc 10 Important

Misc 11

Misc 12

Misc 13 Important

Misc 14

Misc 15 Important

Misc 16 You are here

Misc 17 Important

Misc 18 Important

Misc 19

Misc 20 Important

Last updated at May 29, 2018 by Teachoo

Misc, 16 If (x + iy)3 = u + iv, then show that u/x + v/y = 4 (π₯2 β π¦2) . We know that (π + π)^3 = π3 + π3 +3ππ (π + π) Replacing a = x and b = iy (π₯ + ππ¦)3= π₯3 + (ππ¦)3 + 3 π₯ ππ¦ (π₯ + ππ¦) = π₯3 + π3π¦3 + 3π₯ π¦π (π₯ + ππ¦) = π₯3 + π2 Γπ π¦3 + 3π₯2π¦π+ 3π₯π¦2π2 Putting π2 = β1 = π₯3 + (β 1 Γ π Γ π₯π¦2) + 3π₯2 π¦π + 3π₯π¦2 π₯(β1) = π₯3 β ππ¦3 + 3π₯2 π¦π β 3π₯π¦2 = π₯3 β 3π₯π¦2 β ππ¦3 + 3π₯2π¦π = π₯3 β 3π₯π¦2 + 3π₯2π¦π β ππ¦3 = π₯3 β 3π₯π¦2 + (3π₯2π¦ β π¦3)π Hence, (π₯ + ππ¦)3 = π₯3 β 3π₯π¦2 + (3π₯2π¦ β π¦3)π But, (π₯ + ππ¦)3 = π’ + ππ£ So, π₯3 β 3π₯π¦2 + (3π₯2π¦ β π¦3)π = π’ + ππ£ Comparing Real parts π₯3 β 3π₯π¦2 = π’ π₯ (π₯2β 3π¦2) = π’ π₯2 β 3π¦2 = π’/π₯ Adding (1) & (2) i.e. (1) + (2) π’/π₯ + π£/π¦ = (π₯2 β 3π¦2) + (3π₯2 βπ¦2) = π₯2 β 3π¦2 +3π₯2 β π¦2 = 4π₯2 β 4π¦2 = 4 (π₯2 β π¦2) Thus, u/x + v/y = 4 (x2 β y2) Hence Proved